Micromagnetic simulation of microstructure effect for binary-main-phase Nd–Ce–Fe–B magnets. (19th August 2021) - Kim, C; Liang, D; Han, Y; Ding, S; Li, K; Yun, C; Yang, W; Han, J; Liu, S; Du, H; Wang, C; Yang, J
Abstract: We investigate the magnetic properties of a chemically heterogeneous binary-main-phase (BMP) Nd–Ce–Fe–B magnet with a core–shell structure via micromagnetic simulation. It is found that the coercivity strongly depends on the shell thickness. The BMP magnet's coercivity initially increases and then decreases with increasing Nd-rich shell thickness, and so there is the optimal shell thickness which shows the maximum coercivity for any given Ce concentration. The simulation shows the significant difference in coercivity and maximum energy product between the BMP and single-main-phase magnets. Notably, the magnetization reversal mechanism of the BMP magnet is revealed in the simulation. Local reversals in the BMP magnet first occur in the Ce-rich shells, followed by the Nd-rich cores. Then, the magnetization in Ce-rich core/Nd-rich shell typed grains is switched after reversed magnetization of all the Nd-rich core/Ce-rich shell typed grains. The BMP magnet represents a further increased coercivity for a larger GB thickness, which can be well explained by a maximum stray field.